Challenges and Strategies for Small Business Survival - Hasyim, Hasyim; Bakri, Muhammad (Magister Manajemen Universitas Yapis Papua, 2023)
This literature review explores the primary challenges small businesses face and the strategies they employ for survival, focusing on financial constraints, managerial inefficiencies, and market competition. By synthesizing recent academic research and industry reports, this review provides a comprehensive understanding of small business survival factors. The methodology systematically analyzes current literature to identify effective strategies and integrate theoretical and empirical insights. Small businesses need help accessing financial resources, often facing hurdles with traditional financial institutions due to perceived risks and insufficient collateral. The COVID-19 pandemic has exacerbated these economic challenges. Innovative financing solutions, such as crowdfunding, microloans, and venture capital, have emerged as viable alternatives. Managerial inefficiencies stemming from a lack of formal training further hinder small business success. Continuous skill development and mentorship programs are crucial for enhancing managerial competencies. Additionally, small businesses must navigate intense market competition, necessitating constant innovation and digital transformation. Digital tools and platforms improve competitive advantage and customer engagement. The findings highlight the need for multifaceted strategies addressing financial, managerial, and competitive challenges. Policymakers should facilitate access to alternative financing and support frameworks for small businesses. Future research should explore these factors' dynamic interplay to develop tailored interventions supporting small business growth, contributing to economic development and sustainability.